How Can We Make Scientific Events More Inclusive? Insights From Q&A Sessions and Surveys From an International Conference - Rebecca S. Chen; Tuba Rizvi; Ane Liv Berthelsen; Anneke J. Paijmans; Avery L. Maune; Barbara A. Caspers; Bernice Sepers; Isabel Damas‐Moreira; Isabel Schnülle; Jana Könker; Joseph I. Hoffman; Joelyn deLima; et al. (Ecology and Evolution)
ABSTRACT Despite growing awareness of the importance of researcher diversity, barriers to inclusion and equity persist in science and at academic conferences. As hosts of the 37th International Ethological Congress, “Behaviour 2023”, we studied gender disparities that unfold during question‐and‐answer (Q&A) sessions using observational and experimental behavioural data and surveys. We further used the surveys to investigate broader equity, diversity and inclusivity (EDI) issues at conferences in general. Attendees perceived as women asked fewer questions than those perceived as men because they raised their hands less often to ask questions, and not because they were chosen less often by the session host. Self‐reports indicated that self‐identified women felt more comfortable asking questions when their own gender was represented (in the audience, by the speaker, and/or by the host) and when the setting was smaller. However, this pattern was not reflected in the observational data as perceived women asked fewer questions regardless of the situation. We report potential reasons why women asked fewer questions using survey data, and experimentally tested whether we could reduce gender disparity in question‐asking. Our results indicate that session hosts cannot mitigate the gender disparity in question‐asking by actively selecting perceived women to start the Q&A session. We addressed further inclusivity barriers of underrepresented minorities beyond gender in a post‐congress survey, which showed that underrepresented minorities did not have a more positive or negative congress experience but did perceive EDI issues as more severe. We conclude by providing recommendations for organising more inclusive scientific events.